A Study on the Existentialist Elements in Arun Joshi’s Novels (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This paper focuses on the style and techniques adopted by the selected novelists to unravel the plot and bring out the identity crisis of the characters in the selected novels. Existentialism as a philosophical and cultural movement began in the mid-19th century. The existential elements of loneliness and isolation, the problem of finding meaning within existence are significantly present in his prominent works, The Stranger and The Plague. Existentialism has also been successfully explored in Indian English literature. The Indian English novelists have attempted to explore the individuality of man, his self-examination and search for his identity, his refusal to accept the traditional values propagated by religion or philosophy.